Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.